Sr AND Nd ISOTOPES IN HYDROGENETIC FERROMANGANESE CRUSTS FROM THE NORTH PACIFIC - Pavel E. Mikhailik; Irina A. Vishnevskaya; Evgeniy V. Mikhailik; Vladimir A. Rashidov; Dmitry P. Savelyev; Natalya G. Soloshenko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
The relevance of the study is caused by the need to get knowledge of the fundamental scientific problem – the ferromanganese precipitation of the World Ocean. Marine ferromanganese deposits are records of sedimentation conditions in the past as well as promising mineral raw materials. Their formation is carried out under various processes, which are reflected in the bulk and isotopic composition of ferromanganese deposits. Currently, the least studied region of the Pacific Ocean is its northern segment. The main aim of the research is to study Sr and Nd isotopic composition of the ferromanganese crusts from the northern Pacific, formed under low detrital influx. Methods: litho-morphology; x-ray diffraction – determination of the mineral composition; mass spectrometric – determination of the chemical and isotopic composition. Results. Ferromanganese deposits of the guyots of the northern part of the Imperial Range (Detroit, Suzei, Hanzei) and the Amliya, Rat and Stailmate fracture zones, as well as the Vulkanolog Guyot (Magellan Seamounts), as a comparative material, were studied. Based on the mineralogical and geochemical bulk compositions, the studied ferromanganese deposits are classified as hydrogenetic ferromanganese crusts. The strontium isotopic composition of the studied samples is in the range from 0,70797 to 0,70919 (average 0,70885), with most of the samples concentrated at 0,709. At the same time, the content of strontium changes almost three times from 660 to 1700 ppm. The dependence of the isotopic composition on the concentration is not observed. The displacement of 87Sr/86Sr occurs towards volcanic rocks, which reflects the high amount of quartz-plagioclase admixture in the sample. The isotopic composition of neodymium, in terms of εNd, varies in the range from –3,5 to –3,0, which corresponds to the modern deep seawater of the North Pacific. An increase in εNd to –2,3 corresponds to a sample with the maximum terrigenous admixture. The minimum value of εNd (–4,4) was found in the bottom layer of the ferromanganese crust from the Hanzei Guyot. This value corresponds to the Miocene North Pacific Deep water. This is a reason to believe that in the Miocene the formation of the bulk composition of the North Pacific ferromanganese crusts was under North Atlantic Deep Waters entering through the Panama Gateway. The end of North Atlantic Deep Waters delivery to the Pacific was finished about five million years ago.